ANALISIS DAERAH BINTIK MANIS PADA PERANCANGAN RAKET BULUTANGKIS - Bagus Budiwantoro; I Wayan Suweca; Roby C. M Sibuea (Mesin, 1998)
One method to increase badminton racket performance is by improving individual player's racket. For this purpose, two measurements are necessary, i.e. (1) the racket 's location of sweet spot that is inherent due to its manufacturing process and (2) the players "sweet spot", i.e. the spot that the player consistently hit the badminton cock, which for factory manufactured racket is not the racket 's inherent sweet spot. If the two spots do not coincide, than the original racket meet spot can be shi/ted until it coincides with the player sweet spot, making the racket performance to be maximised.